2023
DOI: 10.1002/oby.23813
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term effects of childhood adiposity on depression and anxiety in adulthood: A systematic review

Abstract: ObjectiveThis review aimed to evaluate the association between childhood adiposity and depression and anxiety risk in adulthood.MethodsMEDLINE, PsychInfo, Embase, CINAHL, and Scopus were searched on June 6, 2022, to identify studies that investigated the association between childhood weight status (age ≤18 years) and outcomes of depression and/or anxiety in adulthood (age ≥19 years). Study quality was assessed using the Newcastle‐Ottawa Scale and results were narratively synthesized.ResultsSixteen studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Several studies have shown that individuals who are obese are more likely to experience mental health difficulties, including social anxiety and depression. [37][38][39] Inversely, patients who achieve weight loss have reported significant improvements in anxiety and depressed mood. 35 Consistent with current evidence, 40,41 our analysis showed that EI training can improve decision-making, impulse control, and stress management, 3 of the 5 scales of the EQi.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that individuals who are obese are more likely to experience mental health difficulties, including social anxiety and depression. [37][38][39] Inversely, patients who achieve weight loss have reported significant improvements in anxiety and depressed mood. 35 Consistent with current evidence, 40,41 our analysis showed that EI training can improve decision-making, impulse control, and stress management, 3 of the 5 scales of the EQi.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood overweight or obesity (OWO) poses significant medical and public health burdens across several countries, including Taiwan [1–5]. Children with OWO have increased risks of type 2 diabetes, dyslipidemia, hypertension, cardiovascular diseases, and premature death in adulthood [6–10].…”
Section: Introductionmentioning
confidence: 99%